Inequality and Welfare by Food Expenditure Components. (The Pakistan Development Review, 2009)
This paper examines inequality and welfare in food consumption expenditure in Pakistan. The indices are derived on the basis of Sen’s welfare function by employing HIES, 2005-06. The empirical results show that inequality and welfare varied widely in urban and rural areas. It can be seen that the concentration index of non essential/luxury food components are unevenly distributed over the total expenditure in favour of rich families. The price elasticity of welfare indicates that rising prices of food components have negative effect on the aggregate welfare. The present analysis provides a basis for determining the magnitude of inequality and welfare that can help in designing appropriate policies. JEL classification: D12, D13, D31, I31 Keywords: Food Consumption, Inequality, Welfare, Elasticity